The overview of channels, transporters, and calcium signaling molecules during amelogenesis. (September 2018) - Kim, Hee-Eun; Hong, Jeong Hee
Highlights: Tooth formation is a dynamic system involving the regulation of electrolyte concentrations by enamel epithelia. Current understanding of how the ion channels and transporters during the amelogenesis handle the homeostasis of electrolytes. The modulation of electrolytes balance by ion transporters apparently provides both morphological and functional stability to achieve appropriate tooth hardness. Abstract: Enamel is a highly calcified tissue. Its formation requires a progressive and dynamic system for the regulation of electrolyte concentration by enamel epithelia. A critical function of enamel epithelial cells, ameloblasts, is the secretion and movement of electrolytes via various channels and transporters to develop the enamel tissue. Enamel formation generates protons, which need to be neutralised. Thus, ameloblasts possess a buffering system to sustain mineral accretion. Normal tooth formation involves stage-dependent net fluctuations in pH during amelogenesis. To date, all of our information about ion transporters in dental enamel tissue is based solely on immunostaining-expression techniques. This review critically evaluates the current understanding and recent discoveries and physiological role of ion channels and transporters, Mg 2+ transporters, and Ca 2+ regulatory proteins during amelogenesis in enamel formation. The ways in which ameloblasts modulate ions are discussed in the context of current research for developing a novel morphologic-functional model of enamel maturation.